Computer aided school administration system using RFID technology - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
The RFID technology has been received a growing attention and has gotten a wide range of applications. Administration systems for automatically managing routine have-to-do works of school staff and students with the aid of computers are one of them. This study focuses on implementing an automation/management system which eases the supervision of students and reduces the burden on school administration staff. In this study a sample school administration system using RFID tags/readers is developed. This system is capable of automatic person identification, class/laboratory/library attendance management, static/dynamic authorization, submission of warnings/announcements, e-money usage, logging and reporting. Due to provide robustness and long lasting run a more server independent structure is designed. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Computer aided; school administration; student supervision; educational technology; rfid